Effects of Problematic Internet Use (PIU) and Psychological Well-Being in Adolescents with Social Anxiety - THAHIR, ANDI; BULANTIKA, SITI ZAHRA; SYUKRON, BUYUNG; SARI, PERMATA (International Journal of Psychosocial Rehabilitation, 2020)
One anxiety that can occur in adolescents/individuals is when doing social interactions. Individuals with social anxiety experience fear in social interaction, will withdraw from association, try to communicate as little as possible, and want to talk when pressed. The cause of social anxiety there are two factors, internal factors, and external factors. Internal factors include the physical and psychological conditions of individuals that are reflected in psychological well-being, while external factors are factors that exist outside of the individual that can be in the form of environmental conditions related to technology and the internet. The purpose of this study was to determine the effect of Problematic Internet Use (PIU) and Psychological Well-Being on adolescent students with Social Anxiety at SMA N 14 Bandar Lampung. The subjects in this study were 120 students of class X. In the study using the GPIUS2 scale developed by Caplan (2003), the psychological well-being scale was made based on aspects of Psychological Welfare, according to Ryff (1989) and the social anxiety scale La Greca & Lopez (1998) Social Anxiety Scale for Adolescents (SAS-A). The data analysis technique used in this study is multiple regression. The results of multiple regression tests showed a significance value of 0,000 (p <0.05). These results indicate that problematic internet use (PIU) and psychological well-being affect adolescents with social anxiety. In adolescents with social anxiety requires mastery of the environment, beliefs, competence in managing emotions and the use of the internet where and when it should.